Unique Foreign Body Chest Diagnosed Incidentally - Wahid, I Fazal; Khan, Muhammad Riaz; Khan, Adil; Ahmad, Iftikhar (Nepalese Journal of ENT Head and Neck Surgery, 2014)
DOI: http://dx.doi.org/10.3126/njenthns.v3i2.10159 Nepalese Journal of Head and Neck Surgery Vol.3(2) 2012: 19-20